Estimating Potential Employment Impact of the Charging Infrastructure used to Support Transportation Electrification in the United States. Issue 12 (December 2022) - Ke, Yue; Mintz, Marianne; Zhou, Yan
Increased concern over greenhouse gas (GHG) emissions and climate change is encouraging many states, companies, and consumers to focus on zero emission vehicle technologies such as electric vehicles (EVs). A major barrier to widespread EV adoption, however, is range anxiety as there is currently insufficient electric vehicle supply equipment (EVSE) available. Although not the primary goal primary of EVSE installations, one of their side effects and a goal of President Biden's infrastructure plans is their impact on employment, both initially as stations are developed and activated and over time and as they continue to provide charging to a growing population of EVs. This study estimates the potential employment effects of the deployment and operation of President Biden's goal of installing 500, 000 charger plugs. To do this, we develop an input-output (IO) based model called JOBS EV. Unlike existing analyses, JOBS EV includes both the employment effects caused by the front-of-meter EVSE equipment needed at a particular site and the back-of-meter or upstream equipment used to obtain power from the existing utility's distribution network. The model results indicate that approximately 1.1 million new jobs will be created over a 10-year period. The modeling process outlined in this paper, in addition to the results presented, may be useful to stakeholders involved in transportation decarbonization efforts as another means of evaluating the costs and benefits of pursuing electrification. Further work is needed to improve the underlying IO model to better account for nascent industries, to accurately calculate local share percentages, and to capture the employment effects of the complete EVSE life cycle.